Trained autologous cytotoxic T-cells derived from PBMCs or splenocytes for immunotherapy of neuroblastoma - Wu, Xiaofang; Basu, Mousumi; Wright, Sarah L.; Li, Samuel; Petrosyan, Mikael; Nelson, Marie V.; Halpern, Alex I.; Shea, Douglas; Yarmakovich, Mark; Sandler, Anthony D. (Frontiers in Immunology, 2025)
BackgroundPediatric solid tumors, particularly neuroblastoma, present significant treatment challenges due to the limited efficacy of existing therapies. Adoptive immunotherapy, which involves transferring immune cells has shown clinical promise. Optimizing the preparation of immune cells ex vivo is critical to enhancing tumor immunity. This study introduces a novel method for improving the efficacy of autologous peripheral blood mononuclear cells (PBMCs) for neuroblastoma treatment.MethodsAn IRB-approved protocol was used to collect tumor samples and PBMCs from eight patients undergoing neuroblastoma biopsy or resection. Primary tumor cells were isolated, cultured, and characterized using Phox2b and synaptophysin staining. Autologous PBMCs were co-cultured with irradiated tumor cells pre-treated with MYC inhibitors (I-BET726, JQ1) and a STING antagonist (C170) to enhance immunogenicity and train tumor-specific PBMCs. The immunogenicity and gene expression changes in treated tumor cells were assessed through multiplex ELISA and NanoString Tumor Signaling profiling. The phenotype and cytotoxicity of the trained PBMCs were evaluated by flow cytometry, IFN-γ ELISA, and IncuCyte assays.ResultsTrained PBMCs primarily induced potent tumor cell cytotoxicity in patient-derived cellular products. In a preclinical neuroblastoma mouse model, similarly trained splenocytes demonstrated powerful efficacy, mirroring the findings in patient-derived PBMCs. This approach generates immunogenic tumor cells through modulation with small molecule inhibitors and radiation, enabling PBMCs or splenocytes to induce cytotoxic trained autologous tumor-specific T cells under controlled in vitro conditions. These trained PBMCs and splenocytes exhibit potent cytotoxicity against neuroblastoma, with significant therapeutic effects as an adoptive cellular immunotherapy in vivo.ConclusionsThis study provides preliminary evidence supporting the efficacy of a personalized, PBMC-based immunotherapy for neuroblastoma. These findings highlight the potential for further development of this approach as a novel treatment strategy, paving the way for improved clinical outcomes in pediatric oncology.